Size-dependent photo-induced shift of the first exciton band in CdTe quantum dots in glass prepared by a two-stage heat-treatment process - Yukselici, M. H.; Allahverdi, C. (ELSEVIER SCIENCE BV, 2008)
CdTe nanocrystals were grown from commercially available RGS50 Schott filter glass by two-step heat-treatment process which almost doubles the particle to matrix volume fraction. A calculation shows that a quantized-state effective mass model in the strong confinement regime might be used to deduce the average radius for the nanocrystals larger than 2 nm in radius from the energetic position of the first exciton peak in optical absorption spectrum. Size-induced shift of similar to 360meV in the first exciton peak position was observed. The steady state photoluminescence spectra exhibit a broad band red shifted relative to the first exciton band, which indicates the existence of shallow trap states. The non-linear optical properties of CdTc nanocrystals were studied by room temperature resonant pbotoabsorption spectroscopy. The differential absorption spectra had three-lobed structure whose size-dependent evolution was explained by bleaching of the absorption, red shift and broadening in the Gaussian absorption band used to fit the first exciton peak. A maximum red shift of 2.32 meV for the average nanocrystal radius of 4.65 nm was estimated by fitting the photomodulation spectra with a combination of first and second derivative Gaussian absorption bands. We presume that the red shift is induced by the electric field of trapped charges in surface states. Internal electric field strengths of 23 and 65kV/cm were predicted for the average nanocrystal radii of 3.95 and 4.65 nm, respectively, with the help of second-order perturbation theory in the strong confinement limit. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: quantum dots; photomodulation spectroscopy; CdTe nanocrystals; diffusion-limited growth; SEMICONDUCTOR-DOPED GLASSES; ELECTROOPTICAL PROPERTIES; MODULATION SPECTROSCOPY; CD(S,SE) NANOCRYSTALS; STATES; MICROCRYSTALLITES; PRECIPITATION; Optics